Full Aperture CO2 Laser Process to Improve Laser Damage Resistance of Fused Silica Optical Surface - Wei Liao; Chuanchao Zhang; Xiaofen Sun; Lijuan Zhang; Xiaodong Yuan (Advances in Condensed Matter Physics)
An improved method is presented to scan the full-aperture optical surface rapidly by using galvanometer steering mirrors. In contrast to the previous studies, the scanning velocity is faster by several orders of magnitude. The velocity is chosen to allow little thermodeposition thus providing small and uniform residual stress. An appropriate power density is set to obtain a lower processing temperature. The proper parameters can help to prevent optical surface from fracturing during operation at high laser flux. S-on-1 damage test results show that the damage threshold of scanned area is approximately 40% higher than that of untreated area.